RANCANG BANGUN PROTOTYPE SISTEM PENGENDALIAN SUHU DAN KELEMBABAN PADA RUMAH TELUR BLACK SOLDIER FLY (BSF) - Fransna, Adilah Devira; Amilia, Winda; Rusdianto, Andrew Setiawan (Jurnal Penelitian Sains dan Teknologi Indonesia, 2024)
Black soldier fly (Hermetia illucens) is a vital organism in waste bioconversion, and optimizing its breeding environment can enhance its effectiveness. This study investigates the development of a prototype system designed to regulate temperature and humidity in the egg-laying area to improve the living conditions for breeding black soldier flies. The research evaluates the prototype through several parameters: tool functionality, sensor performance, and egg production outcomes. Field tests confirm that the prototype effectively maintains the ideal conditions necessary for the mating process of black soldier flies. The functionality testing showed that the prototype achieved a functionality score of 1, indicating compliance with the ISO/IEC 9126 standards for software quality. Regarding sensor performance, the DHT22 sensor used for temperature monitoring demonstrated an average relative error of 4.49% and an absolute temperature error of 1.33°C. For humidity measurements, the sensor showed an average difference of 0.63% relative humidity (RH), with the maximum observed error being 1% RH. In terms of egg production, observations revealed a notable increase following the introduction of the control system. The egg yield improved significantly from an initial 43 grams to 151 grams, highlighting the positive impact of the prototype on reproductive performance. Overall, the study concludes that the prototype system is effective in creating a controlled environment that enhances the breeding conditions for black soldier flies. This improvement not only supports the flies' mating process but also boosts their productivity, thereby contributing to their efficiency as waste bioconversion agents.